PENGARUH KREATIVITAS GURU DALAM PEMBELAJARAN DAN KECERDASAN EMOSIONAL SISWA TERHADAP PRESTASI BELAJAR EKONOMI PADA SISWA KELAS X DI SMA NEGERI 89 JAKARTA - Saptono, Ari (Jurnal Ilmiah Econosains, 2016)
This study aims to determine the influence of teacher’s creativity in learning and emotional intelligence of students on student achievement in class X peminatan IIS in SMA 89 Jakarta, either partially or simultaneously. This study used survey method with quantitative approach. Collecting data using a document recording techniques, observation and questionnaires. The population in this study were students of class X peminatan IIS which numbered 137 students to the overall sample. Data analysis technique used is multiple linear regression, and hypothesis testing consisting of t test and F. Based on the results of data analysis known that there was a partial effect between the creativity of teachers in teaching with student achievement. Can be seen from the results of data analysis showed t value of 3.926 is greater than t table of 1.656. Emotional intelligence of students partially also there is an influence on student achievement, it is seen from the results of data analysis showed t value of 2.611 is greater than t table of 1.656. Simultaneously there is influence between the creativity of teachers in the learning and emotional intelligence of students on student achievement. Can be seen from the results of data analysis showed calculated F value of 18.002 is greater than the value of F table 3,06. There are positive influence between the creativity of teachers in the learning and emotional intelligence of students on student achievement with multiple correlation coefficient 0.460 thus, the research hypothesis is accepted, then known coefficient of determination (R 2) of 21.2%.